Investing in Education and Scientific Research for Growth of Iraq: Exploring the Main Dimensions, Success Factors, and Government Policies - Abdulrazaq Abdulkarem *, Hayder; Mohammed Hasan , Adnan (Journal of Economics and Administrative Sciences, 2024)
The research aims to explore the dynamics of investment in education and scientific research and their influence on Iraq’s economic growth. Utilizing a descriptive-analytical approach, the study focuses on various dimensions of education and research investment, including quality education, vocational training, funding, infrastructure, collaboration, and government policies. The data was collected through a comprehensive survey, designed based on international standards and tailored to the specific context of Iraq. The survey garnered 191 valid responses from a diverse range of stakeholders in Iraq’s education and research sectors, including educators, policymakers, academic researchers, and institutional representatives. The statistical analysis was carried out using specialized software (Amos.V24 and SPSS.V26), incorporating methods such as arithmetic averages, standard deviation, coefficient of difference, and relative importance. The study also includes visual representations such as bar charts and heat maps to elucidate the findings. The most prominent result emphasizes the strong positive correlation between investment in education, research, and economic development in Iraq. It underscores the necessity for a concerted effort to improve education quality, fostering scientific research, and aligning it with the country’s economic development goals. The findings affirm that strategic investment in education and research can catalyze Iraq’s growth and progress.